The Implementation of Quizizz Paper Mode to Improve Vocabulary Mastery at SD Negeri 52 Pinrang - Besse Ummi Kalsum; Arqam; Abdul Haris Sunubi; Mujahidah; Magdahalena (Universitas Muhammadiyah Palu, 2025)
This study examines the implementation of Quizizz Paper Mode as a digital-based learning tool aimed at improving vocabulary mastery among fourth-grade students at SD Negeri 52 Pinrang. The study was motivated by the lack of student interest and performance in vocabulary learning due to traditional and monotonous teaching methods. A pre-experimental design was used involving a single group of 25 students who completed a pre-test, participated in four treatment sessions using Quizizz Paper Mode, and took a post-test. The study focused on two aspects of vocabulary: word meaning and word use. The results showed a substantial improvement in students’ vocabulary mastery. In word meaning, the percentage of students in the “Poor” category dropped from 80% to 32%, while those achieving “Very Good” increased from 4% to 20%. In word use, the “Poor” category decreased from 96% to 12%, and 36% of students reached “Very Good.” These findings indicate that Quizizz Paper Mode is an effective and engaging method for vocabulary instruction, especially in low-tech classrooms. The integration of game-based elements and real-time feedback made the learning process more interactive and enjoyable. Therefore, it can be concluded that the use of Quizizz Paper Mode not only significantly improves students’ vocabulary mastery but also increases their motivation and active participation in learning. This method is a promising and innovative alternative for English instruction in primary schools, particularly in low-tech learning environments.